Unlocking Potiential Exploring the transformative power of generative leadership in fostering creativity and positive change - Vanita Mane (Pune Tathwade, 2024)
Organizations are increasingly recognizing the importance of supporting innovation and constructive change to maintain competitiveness in today's evolving business environment. Leadership plays a role in shaping the potential of teams and organizational culture. In this research paper, we aim to explore how generative leadership can unlock creativity and drive change within an organization, By examining the principle of characteristics of leadership our study provides valuable insights into how leaders can foster an environment that stimulates innovation and cultivates a forward-thinking mindset Through case studies empirical evidence and relevant literature analysis. The paper comprehensively examines the impact of leadership on driving changes and promoting organizational innovation.
Keywords: Organizational Culture; Creativity; Positive change; Employees Engagement